Students’ Perceptions of Synchronous Online Learning using Google Meet in a Reading Class - Azizatuz Zahro Al Faruq; Ngadiso Ngadiso; Slamet Supriyadi (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this research is to investigate the students’ perceptions of synchronous online learning using Google Meet. Synchronous online learning is applied to facilitate the students to acquire knowledge during this pandemic. However, the students’ perception of the synchronous online using Google Meet in a specific skill in ELT is still understudied. A qualitative case study was used to investigate this phenomenon. The participants of this study were 18 students in the first semester who were Electrical Engineering major. The participants were chosen purposively due to class participation and willingness. The data was gathered from the questionnaire and interviews. It was analyzed using the Interactive Model of Data Analysis. This study exposed that the students positively perceived implementing synchronous online learning using Google Meet in reading class. They pointed out that it could help the students read more and feel motivated to be active. It also aided to increase their reading by online discussion. However, they found some challenges which they perceived during synchronous online learning. The challenges came from environmental, technical, and personal problems. The implication of this study relates to continuing the teaching-learning process of synchronous online learning using Google Meet. It provides some benefits that support the teaching learning process. Then, the institution and the government should support and promote the effectiveness of synchronous online learning by improving their learning and providing the necessary learning infrastructure for all students.